Extension Education: New Horizons - R.Vasantha; S. Kiran (Ludhiana Kalyani, 2012)
This book, by virtue of its practical approach, Will also be very useful for variou categories of personnel engaged in education of both students and farmers.
Programme Development Process Watershed Farming System
Keywords: Programme Development Process, Watershed ,Farming System